2022
DOI: 10.3389/fnins.2022.858070
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Dynamics in the Body and Brain Regulated by the Receptor for Advanced Glycation End-Products, CD38, CD157, and Nicotinamide Riboside

Abstract: Investigating the neurocircuit and synaptic sites of action of oxytocin (OT) in the brain is critical to the role of OT in social memory and behavior. To the same degree, it is important to understand how OT is transported to the brain from the peripheral circulation. To date, of these, many studies provide evidence that CD38, CD157, and receptor for advanced glycation end-products (RAGE) act as regulators of OT concentrations in the brain and blood. It has been shown that RAGE facilitates the uptake of OT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 119 publications
(173 reference statements)
0
7
0
Order By: Relevance
“…While initial studies in animal models concluded that the BBB is relatively impermeable to OXT ( Mens et al, 1983 ; Kendrick et al, 1986 ), recent studies have demonstrated that it can be transported into the brain by binding to the receptor for advanced glycation end products (RAGE) in BBB endothelial cells ( Yamamoto et al, 2019 ; Yamamoto and Higashida, 2020 ; Munesue et al, 2021 ), with in vitro studies also reporting the presence of this potential transport system in humans (see Higashida et al, 2022 ). Compared to wild-type controls, RAGE knock-out mice do not exhibit increased OXT in the brain following intranasal or subcutaneous administration ( Yamamoto et al, 2019 ; Munesue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While initial studies in animal models concluded that the BBB is relatively impermeable to OXT ( Mens et al, 1983 ; Kendrick et al, 1986 ), recent studies have demonstrated that it can be transported into the brain by binding to the receptor for advanced glycation end products (RAGE) in BBB endothelial cells ( Yamamoto et al, 2019 ; Yamamoto and Higashida, 2020 ; Munesue et al, 2021 ), with in vitro studies also reporting the presence of this potential transport system in humans (see Higashida et al, 2022 ). Compared to wild-type controls, RAGE knock-out mice do not exhibit increased OXT in the brain following intranasal or subcutaneous administration ( Yamamoto et al, 2019 ; Munesue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that functional effects of both intranasal and subcutaneous OXT do not occur in RAGE knockout mice and increased brain concentrations of OXT are prevented [65][66][67]. In vitro studies have also reported the presence of this potential transport system in humans [68]. Another potential mechanism is that increased peripheral OXT concentrations act on its receptors in the heart and gastrointestinal system to promote vagally-mediated stimulation of the brain [23,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…At such doses, oxytocin could also pass directly into the brain via the blood-brain barrier. In addition, afferent stimulation of sensory nerves by peripheral oxytocin could also promote central oxytocin release [ 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%